Response to External Radiation and Interstitial Brachytherapy in Bulky Vulvar Cancer - I.A.Trisna Kumala Dewi; Sri Mutya Sekarutami (Radioterapi & Onkologi Indonesia, 2020)
Vulvar cancer is a gynaecologic malignancy with an incidence of 3-5% of all gynaecologic malignancies. In Indonesia, number of new cases of vulvar cancer reaches 1153 cases with a mortality rate of 420. Multimodal therapy is the main therapy of vulvar cancer at advanced stage which consists of of surgery, radiotherapy, and chemotherapy. The role of brachytherapy as adjunctive therapy combined with EBRT is widely studied, especially its role in the management of patients with comorbidities or contraindications to surgery. The purpose of writing this case report is to assess the response of radiotherapy in the form of external beam radiotherapy (EBRT) and brachytherapy use the MUPIT applicator in patients with vulvar cancer. From the relevant studies, we obtain a good 5-year overall survival rate, disease free survival rate, and local control with tolerable complications. It can be concluded that the combination of EBRT and brachytherapy can be one of the therapeutic modality of choice in vulvar cancer.